Aspect of fatigue analysis of composite materials: a review - Mat Jusoh, Suriani; Ali, Aidy; Salit, Mohd Sapuan; Abdan, Khalina (Universiti Putra Malaysia Press, 2013)
This paper reviewed the aspect of fatigue approaches and analysis in a fibre reinforced composite materials which have been done by researchers worldwide. The aim of this review is to provide a better picture on analytical approaches that are presently available for predicting fatigue life in composite materials. This review also proposes a new interpretation of available theories and identifies area in fatigue of natural fibre reinforced composite materials. Thus, it was concluded there are still very limited studies on fatigue analysis of natural fibre reinforced composite materials, especially using non-destructive technique (NDT) methods and a new mathematical modelling on fatigue should be formulated.